O diário visual das memórias a partir do livro de artista : uma proposta de ensino aprendizagem desenvolvida no PARFOR - Moreno, Márcia (2017)
The article "The Diary of Visual Memory based on the Artist's Book: a proposal of teaching and learning developed at the PARFOR", is a result of research developed in the Visual Arts -- Graduation Course of Unochapecó (PARFOR). The objective was to understand the concepts and the importance of the elaboration of an artist's book for the visual registration and the recovery of moments lived by Primary School Students